CD8+ T cells with distinct cytokine‐producing features and low cytotoxic activity in eosinophilic and non‐eosinophilic chronic rhinosinusitis with nasal polyps. Issue 9 (16th June 2016) - Ma, J.; Shi, L.‐L.; Deng, Y.‐K.; Wang, H.; Cao, P.‐P.; Long, X.‐B.; Zhang, X.‐H.; Liu, Y.; Zeng, M.; Liu, Z.
Summary: Background: CD8 + T cells are important effectors of cell‐mediated immunity; however, their contribution to the pathogenesis of CRS is unclear. Objective: This study aimed to characterize the cytokine‐producing features and cytotoxic activity of CD8 + T cells, and their correlation with inflammation patterns in CRS with nasal polyps. Methods: The expression of IFN‐γ, IL‐4, IL‐5, IL‐17A, forkhead box P3 (FOXP3), perforin, and granzyme B in CD8 + T cells was studied by means of flow cytometry, immunohistochemistry, and immunofluorescence. The expression of CD8 + T‐cell subset relevant chemokines and chemokine receptors was detected by means of real‐time RT‐PCR or ELISA. The cytotoxic activity of sorted CD8 + T cells was defined by anti‐CD3‐redirected killing assay. Results: Compared with controls, elevated percentages of total CD8 + T cells and cytotoxic T lymphocyte (Tc) 1 (IFN‐γ + ), Tc2 (IL‐4 + ), and Tc17 (IL‐17A + ) cell subset, and decreased percentages of FOXP3 + CD8 + regulatory T cells, were found in both eosinophilic and non‐eosinophilic polyps with a Tc2‐skewed and Tc1/Tc17‐dominated response in eosinophilic and non‐eosinophilic polyps, respectively. Nasal CD8 + T cells were found to produce similar or even higher levels of IFN‐γ and IL‐4 compared with CD4 + T cells. Tc1 and Tc17, and Tc2 (IL‐4 + and IL‐5 + ) cell subset percentages positively correlated with neutrophil and eosinophil counts in sinonasal mucosa, respectively. Strikingly, the expression of perforin and granzyme B and cytotoxic activity were significantly reduced in nasal CD8 + T cells compared with their counterparts in peripheral blood. The expression of CXCL16, CCL17, and CCL20 positively correlated with Tc1, Tc2, and Tc17 cell subset number in sinonasal mucosa, respectively. Conclusion and Clinical Relevance: CD8 + T cells have low cytotoxic activity; nevertheless, they are a significant and previously underappreciated source of inflammatory cytokine production in polyps. Different Tc cell subset domination may contribute to distinctly biased granulocyte inflammation in eosinophilic and non‐eosinophilic polyps.